Nature against the Human Species: Science in the Apocalyptic Novels by James Ballard and Olaf Stapledon - Boyarkina, Iren (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The paper focuses on the post-apocalyptic novels by J. G. Ballard The Wind from Nowhere (1961) and Last and First Men by Olaf W. Stapledon (1930), by analysing scientific phenomena and discoveries employed in these novels, in which the novum is used as the springboard for the observations about human nature and human futurity. These novels can serve as a warning to mankind and may be seen as allegorical representations of the breakdown of society facing existential threats. Not only do both writers in these novels use the latest achievements in quantum physics and astrophysics, but they also provide profound psychological analysis of the human species doomed to inevitable extinction. Stapledon and Ballard suggest that negative human features such as unquenchable thirst for money and power, egoism, irresponsibility can also lead to wars and ecological catastrophes causing the extinction of the human species. These novels can serve as a warning to the humankind and as a call to combine the great powers of science, common sense, and the best human qualities in order to solve problems threatening the existence of humankind, from the climate change to a supernova explosion.